2015
DOI: 10.1186/s13052-015-0173-z
|View full text |Cite
|
Sign up to set email alerts
|

Femicide and murdered women’s children: which future for these children orphans of a living parent?

Abstract: BackgroundTo assess the prevalence of femicides in Italy over the last three years and the potential long lasting effects of these traumatic events for the children of a woman who dies a violent death.MethodsThe data used in this study come from an internet search for the number of femicides occurring in Italy between 1st January, 2012 and 31st October, 2014.ResultsThe total number of femicides was 319; the average age of murdered women was 47.50 ± 19.26. Cold arms in the form of sharp object -mostly knives- h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 21 publications
2
22
0
7
Order By: Relevance
“…Median age of femicide victims was relatively low and much lower than victims of other violent deaths, corroborating a study in Porto Alegre 27 and differing from findings in other countries 23,26 . In Italy, for example, more than half of the victims were over 45 years of age 23 .…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Median age of femicide victims was relatively low and much lower than victims of other violent deaths, corroborating a study in Porto Alegre 27 and differing from findings in other countries 23,26 . In Italy, for example, more than half of the victims were over 45 years of age 23 .…”
Section: Discussionsupporting
confidence: 74%
“…Median age of femicide victims was relatively low and much lower than victims of other violent deaths, corroborating a study in Porto Alegre 27 and differing from findings in other countries 23,26 . In Italy, for example, more than half of the victims were over 45 years of age 23 . In addition, our final model showed a protective effect against femicide as women's age increased, suggesting that younger victims are more vulnerable and that femicide may negatively influence premature mortality indicators in these women.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Previous research performed by the same author, Ferrara and colleagues, revealed that the majority of femicides occurred in northern Italy and that the current and former intimate partners were the perpetrators in more than half of the homicide deaths of women in Italy. (13) Prior findings revealed that actual or imminent separation appears to be a high- risk situation, since, in our data, the passionate motive is the most frequent motive behind femicide. Our results are consistent with these findings: 72,6 % of victims were ≤ 60 years old in 2015.…”
Section: Resultsmentioning
confidence: 81%
“…When the filicide is caused by women capable of understanding and taking action, the motives are: life stressor events, pietas (altruistic murder), the mother's immaturity, the fact that the child is hyperac-tive, the fact that the child is perceived as the result of a sinful act, Medea syndrome, personality dis-orders (addicted, narcissistic or histrionic), the fact that the child is unwanted, depression in a narcis-sistic subject, and behavioral disorders due to alcohol and drug abuse. (30,(31)(32)(33)(34) If pathological causes with partial (greatly diminished) or total impairment to understand and take action are present, the motives are: postpartum psychosis, hysteric fundus, major depression, schizophrenia, twilight state, psychotic disorder due to a general medical condition, epilepsy, oligophfrenia, plaque sclerosis, and multiple personality. (30) …”
Section: Classificationsmentioning
confidence: 99%